Interaction between the assembly of the ribosomal subunits: Disruption of 40S ribosomal assembly causes accumulation of extra-ribosomal 60S ribosomal protein uL18/L5. - Nusrat Rahman; Md Shamsuzzaman; Lasse Lindahl (PLoS ONE)
Inhibition of the synthesis of an essential ribosomal protein (r-protein) abrogates the assembly of its cognate subunit, while assembly of the other subunit continues. Ribosomal components that are not stably incorporated into ribosomal particles due to the disrupted assembly are rapidly degraded. The 60S protein uL18/L5 is an exception and this protein accumulates extra-ribosomally during inhibition of 60S assembly. Since the r-proteins in each ribosomal subunit are essential only for the formation of their cognate subunit, it would be predicted that accumulation of extra-ribosomal uL18/L5 is specific to restriction of 60S assembly and does not occur abolition of 40S assembly. Contrary to this prediction, we report here that repression of 40S r-protein genes does lead to accumulation of uL18/L5 outside of the ribosome. Furthermore, the effect varies depending on which 40S ribosomal protein is repressed. Our results also show extra-ribosomal uL18/L5 is formed during 60S assembly, not during degradation of mature cytoplasmic 60S subunits. Finally, we propose a model for the accumulation of extra-ribosomal uL18 in response to the abolition of 40S r-proteins.